Chemopreventive role of Copaifera reticulata Ducke oleoresin in colon carcinogenesis - Senedese, Juliana Marques; Rinaldi-Neto, Francisco; Furtado, Ricardo Andrade; Nicollela, Heloiza Diniz; Ribeiro de Souza, Larissa Daniela; Ribeiro, Arthur Barcelos; Ferreira, Lucas Souza [UNESP]; Magalhaes, Georgia Mode; Carlos, Iracilda Zeppone [UNESP]; Mangabeira da Silva, Jonas Joaquim; Tavares, Denise Crispim; Bastos, Jairo Kenupp (Elsevier B.V., 2019)
In Brazilian folk medicine, copaiba oleoresin is widely known for its therapeutic activity, especially its wound healing and anti-inflammatory actions. Considering the relationship between inflammatory processes and carcinogenesis, this paper reports on the Copaifera reticulata Ducke oleoresin (CRO) chemopreventive potential in the colon carcinogenesis model in rats. To understand the mechanisms involved in this effect, the anti-inflammatory activity of CRO and its major chemical constituent, the diterpene ent-polyalthic acid (PA), were evaluated on the production of nitric oxide (NO) and prostaglandin E2 (PGE2) in mouse macrophages. For the chemoprevention assessment, the effect of CRO administered by gavage was investigated on DNA damage, preneoplastic lesions and mitotic frequencies induced by the 1,2-dimethylhydrazine (DMH; intraperitoneal injection) carcinogen by comet, aberrant crypt focus (ACF) and long-term assays, respectively. CRO reduced DNA damage (average 31.5%) and pre-neoplastic lesions (average 64.5%) induced by DMH, which revealed that CRO has antigenotoxic and anticarcinogenic effects. In the long-term assay, treatment with CRO significantly decreased mitoses in the tumor tissue, which suggested that CRO influenced carcinogenesis progression. PA reduced NO levels induced by lipopolysaccharides in macrophages. However, this diterpene showed no effect on PGE2. Taken together, our results suggest that PA exerts anti-inflammatory action via the NO pathway. The CRO chemopreventive effect may be partly due to the anti-inflammatory property of its major chemical constituent, PA. Our findings indicate that CRO is a promising agent to suppress colon carcinogenesis.
Keywords: Copaifera reticulata Ducke; ent-polyalthic acid; Antigenotoxicity; Anticarcinogenesis; Anti-inflammatory activity